72.9k views
1 vote
Select the expression that has a value of 13. 9 + 3 x (2 ÷ 3) + 6 (9 + 3) x 2 ÷ 3 + 6 9 − (3 x 2) ÷ 3 + 6 (9 + 3 x 2) ÷ 3 + 6

1 Answer

1 vote

Answer:


(c)\ 9 - (3 * 2) / 3 + 6

Explanation:

Given

(a) to (d)

Required

Which equals 13


(a):\ 9 + 3 * (2 / 3) + 6

Solve the bracket


9 + 3 * (2 / 3) + 6 =9 + 3 * ((2)/(3)) + 6

Open the bracket


9 + 3 * (2 / 3) + 6 =9 +2 + 6


9 + 3 * (2 / 3) + 6 == 17


(b):\ (9 + 3) * 2 / 3 + 6

Solve the bracket


(9 + 3) * 2 / 3 + 6 =(12) * 2 / 3 + 6

Open bracket


(9 + 3) * 2 / 3 + 6 =24 / 3 + 6

Divide


(9 + 3) * 2 / 3 + 6 =8 + 6


(9 + 3) * 2 / 3 + 6 =14


(c)\ 9 - (3 * 2) / 3 + 6

Solve the bracket


9 - (3 * 2) / 3 + 6 =9 - (6) / 3 + 6

Remove bracket


9 - (3 * 2) / 3 + 6 =9 - 6 / 3 + 6

Divide


9 - (3 * 2) / 3 + 6 =9 - 2 + 6


9 - (3 * 2) / 3 + 6 =13


(d)\ (9 + 3 * 2) / 3 + 6

Solve the bracket (the product, first)


(9 + 3 * 2) / 3 + 6=(9 + 6) / 3 + 6


(9 + 3 * 2) / 3 + 6=15 / 3 + 6

Divide


(9 + 3 * 2) / 3 + 6=5 + 6


(9 + 3 * 2) / 3 + 6=11

Only (c) equals 13

User Overachiever
by
5.5k points